ANALISIS PREFERENSI SISWA MELANJUTKAN KE SMA SANTA MARIA KECAMATAN SAIL KOTA PEKANBARU TAHUN PELAJARAN 2014/2015 - Lucia Suhartati Rahayu Lucia Suhartati Rahayu; Abu Asyari Abu Asyari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research are: (a) Analyze the internal factors that become the preference of the students in choosing Senior High School, (b) Analyze  the external factors that become the preference of the students in choosing Senior High School, (c) Analyze the category of the students internal preference in choosing Senior High School, (d) Analyze the category of the student external preference in choosing Senior High School. The Method used in this research is a descriptive research, with Cluster Random Sampling. The technique results of thisresearch are: (a) The internal factor that become the preference of students in choosing Senior High School because they wish for the suitable job, and suitable with their hobby, and their own, and want to continuing University (b) The external factor that become the preference of the students in choosing Senior High School because the approval of their parents, achieveable school cost by parents economy ability, and depend the science has general (c) The category of internal preference of students in choosing Senior High School is in high category is 70,44%, (d) The category of external preference of students in choosing is in middle category is 62,89%. Keywords: Preference